Molecularly imprinted polymer particles: synthetic receptors for future medicine. (December 2006) - Schillemans, Joris P; van Nostrum, Cornelus F
Molecular imprinting is a relatively new and rapidly evolving technique used to create synthetic receptors; it also possesses great potential in a number of applications in the life sciences. Traditionally, molecularly imprinted polymers are prepared by bulk polymerization, followed by crushing and sieving to obtain polymer beads. However, several methods can be used to synthesize polymer micro- and nano-particles directly, thereby avoiding the time- and labor-consuming process of crush sieving. Possible applications are foreseen in enhanced drug loading, controlled drug delivery and drug targeting. This review describes the different methods of synthesis of molecularly imprinted micro- and nano-particles and discusses how these methods challenge the outstanding issues that molecular imprinting is facing today, thereby facilitating biomedical applications in the future.